Aligned MHD jeffrey fluid flow containing carbon nanoparticles over exponential stretching sheet with viscous dissipation and newtonian heating effects - Nor Aini Naili Noor, Habib; Nur Syamilah, Arifin; Syazwani, Mohd Zokri; Abdul Rahman, Mohd Kasim (Semarak Ilmu Publishing, 2023)
This study investigates the influence of viscous dissipation on aligned Magnetohydrodynamic (MHD) flow of Jeffry fluid containing Carbon Nanoparticles (CNTs) over an exponential stretching sheet with boundary condition of Newtonian Heating (NH). The model proposed by Tiwari and Das is adopted. The numerical computation using Runge-Kutta Fehlberg (RKF45) method is used to generate the results. The numerical solutions of the several parameters on the velocity and temperature profiles are analysed and presented graphically. It is revealed that an increase in aligned angle, magnetic field, and ratio of relaxation to retardation times leads to the decreasing in velocity and increasing in temperature profiles. Meanwhile, both velocity and temperature profiles increase with a rise in volume fraction parameter.